2021
DOI: 10.7150/ijbs.62168
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Alcohol-related Hepatocellular Carcinoma Prognostic Subtypes based on an Integrative N6-methyladenosine methylation Model

Abstract: Background: Alcohol consumption increases the risk of hepatocellular carcinoma (HCC), and associated with a high mortality rate and poor prognosis. N6-methyladenosine (m6A) methylations play key roles in tumorigenesis and progression. However, our current knowledge about m6A in alcohol-related HCC (A-HCC) remains elucidated. Herein, the authors construct an integrative m6A model based on A-HCC subtyping and mechanism exploration workflow. Methods: Based on the m6A expressions of A-HCC and in vivo experiment, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 90 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…There is increasing evidence that the m 6 A modification has a significant impact on cancers, including HCC, through various mechanisms [65]. It has been reported that METTL3, YTHDF1, HNRNPA2B1, HNRNPC, and RBM15B are overexpressed in HCC, and most of them can lead to a poor prognosis [66][67][68][69], which is similar to our results. In addition, METTL3 promotes the process of HCC by regulating the m 6 A levels of USP7 [70]; the increased expression of YTHDF1 enhances the proliferation of HCC cells, which can be achieved by the connection of circMAP2K4 with HSA-Mir-139-5p [71].…”
Section: Discussionsupporting
confidence: 90%
“…There is increasing evidence that the m 6 A modification has a significant impact on cancers, including HCC, through various mechanisms [65]. It has been reported that METTL3, YTHDF1, HNRNPA2B1, HNRNPC, and RBM15B are overexpressed in HCC, and most of them can lead to a poor prognosis [66][67][68][69], which is similar to our results. In addition, METTL3 promotes the process of HCC by regulating the m 6 A levels of USP7 [70]; the increased expression of YTHDF1 enhances the proliferation of HCC cells, which can be achieved by the connection of circMAP2K4 with HSA-Mir-139-5p [71].…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, a number of cohort studies from TCGA patient samples and other online databases illustrated the expression level of YTH family and its association with the clinical characteristics of some cancer types [ 86 97 ]. We summarized the association and clinical characteristics between YTH family members and various tumors in Table 2 .…”
Section: Yth Domain-containing Proteins Function As M6a Readers In Ca...mentioning
confidence: 99%
“…Finally, the statistics of the filtered datasets are shown in Table 1. The 23 m6A RNA methylation-related genes were acquired from the previous related research [24][25][26][27], including 8 readers, 13 writers, and 2 erasers (Table 2).…”
Section: Downloading Datamentioning
confidence: 99%